2022
DOI: 10.1186/s12943-022-01507-x
|View full text |Cite
|
Sign up to set email alerts
|

A microRNA-based liquid biopsy signature for the early detection of esophageal squamous cell carcinoma: a retrospective, prospective and multicenter study

Abstract: Background Currently, there is no clinically relevant non-invasive biomarker for early detection of esophageal squamous cell carcinoma (ESCC). Herein, we established and evaluated a circulating microRNA (miRNA)-based signature for the early detection of ESCC using a systematic genome-wide miRNA expression profiling analysis. Methods We performed miRNA candidate discovery using three ESCC tissue miRNA datasets (n = 108, 238, and 216) and the candida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 42 publications
(53 reference statements)
0
19
0
Order By: Relevance
“…m5C, as a common RNA modification type, has displayed significant value in the diagnosis of several cancers (9,29). miRNAs have been identified as excellent candidate noninvasive biomarkers because of their high stability and abundance in serum (30,31). Therefore, numerous studies have evaluated the diagnostic potential of various miRNAs, such as miR-320b, miR-125b, miR-221-3p, and miR-124-3p (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…m5C, as a common RNA modification type, has displayed significant value in the diagnosis of several cancers (9,29). miRNAs have been identified as excellent candidate noninvasive biomarkers because of their high stability and abundance in serum (30,31). Therefore, numerous studies have evaluated the diagnostic potential of various miRNAs, such as miR-320b, miR-125b, miR-221-3p, and miR-124-3p (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…First, serum miR-21 expression levels are stable and reproducible. One explanation for this remarkable stability is that miRNAs might be chemically modified ( e.g ., methylation), making them resistant to ribonu-clease activity ( Miyoshi et al, 2022 ). Second, when compared with histopathological examination, serum or plasma miR-21 is characterized by minimal invasion and convenience and easily detected by qRT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the risk assessment tool used in non-incidence areas may not accurately distinguish risk levels, and further risk stratification methods need to be developed to identify high-risk individuals. Numerous studies have indicated that multiple biomarkers such as tumor-associated antigens, autoantibodies, miRNAs, and methylated DNA markers exhibit good performance for the early detection and diagnosis of EC and GC (21)(22)(23)(24)(25)(26). Thus, the combination of epidemiological risk factors (obtained by the questionnaire) and promising biomarkers, which may be used to develop risk prediction models, may help to optimize the risk stratification and improve screening efficacy.…”
Section: Discussionmentioning
confidence: 99%